Evaluation of laparoscopic versus open sacrocolpopexy for vaginal vault prolapse – A study from a tertiary care center - Senthilkumar Poovathai; Rajkumar Ramakrishnan; Rajasekar Sundaram; Sammohit Gulakavarapu; Gopu Rakesh Vamsi; Shravankumar Savadatti (Asian Journal of Medical Sciences, 2023)
Background: Post hysterectomy vault prolapse is a progressive herniation of the vaginal vault through the urogenital diaphragm and commonly leads to per vaginal bulge. Surgically, vault prolapse is corrected by sacrocolpopexy which can be done both as an open abdominal surgery and as a laparoscopic repair. Aims and Objectives: This study was performed to compare the therapeutic efficacies of laparoscopic and abdominal sacrocolpopexy. Materials and Methods: This study includes 50 cases of vault prolapsed who underwent hysterectomy previously, admitted in our institution and operated during January 2021–June 2022 for a period of 18 months with both open abdominal and laparoscopic sacrocolpopexy. We compared the basic characteristics, duration of surgery, post-operative stay, post-operative complications, and patient satisfaction between open and laparoscopic groups. Results: No significant difference was observed between the characteristics of the patients in the abdominal-approach group and the laparoscopic-approach group. The laparoscopic-approach group had a lower intraoperative estimated blood loss (187.8 vs. 90.3 mL, P<0.001) and a shorter operative time (148.0 vs. 115.3 min, P<0.001) than the abdominal-approach group. The complication rates of the two groups were not significantly different. Conclusion: Our Study is favorable for the use of laparoscopic approach over open abdominal surgery for treating cases of vault prolapse for sacrocolpopexy. The less invasive method leads to less blood loss and a shorter operative time than an open approach.